Perceived understanding of supply chain integration, communication and teamwork competency in the global manufacturing companies - Fernando, Yudi; Wulansari, Puspita (Emerald Publsiher, 2020)
Purpose – This study empirically examines a model that describes the direct path from perceived understanding of supply chain integration (PUSCI) to perceived understanding of supply chain responsiveness (PUSCR) to leverage supply chain manager’ s communication and teamwork competencies. This study also examines whether knowledge and task skill and proficiency mediate the relationship between PUSCI and PUSCR to improve the communication and teamwork competency of a supply chain manager. Design/methodology/approach – The data were collected using a survey questionnaire that was mailed to the 413 supply chain managers of global manufacturing companies in Indonesia. Findings – The result from model testing shows that PUSCR significantly and positively affected the communication and teamwork competency of supply chain manager and knowledge, task skill and proficiency as mediating variables improved communication and teamwork competency. The results found that PUSCI was related to supply chain manager’ s competency. Practical implications – Supply chain managers are advised to focus on PUSCI and consistently improve effective communication and teamwork competency. Originality/value – This study will extend the literature by utilizing the competency-based theory to investigate the perceived understanding and communication capabilities of supply chain managers.